The Effect of Fuel Cell Reactor Volume on a Pertalite-Fueled Drive Engine Per 75 ML - Friani Andani Juliana Manoppo; Blest Johnsis Labi; Jedithjah Naapia Tamedi Papia; Nelson Seleman Luppa (International Journal Labs, 2026)
The increasing number of motor vehicles has led to a continuous rise in Pertalite fuel consumption, while petroleum reserves remain limited and non-renewable. One proposed solution is the application of a fuel cell (HHO generator), which utilizes water electrolysis to produce hydrogen and oxygen gases to support the combustion process inside the engine. However, studies examining the effect of fuel cell reactor volume on engine performance remain limited. This study aims to determine the effect of fuel cell reactor volume on the performance of a Pertalite-fueled engine using 75 mL of fuel. The research employed an experimental approach by comparing engine performance without a fuel cell and with a fuel cell equipped with a 180 mL reactor volume (containing an electrolyte solution of 5 g of caustic soda and 180 mL of distilled water, with a current of 3.5 Ah) at three engine speed levels (2000, 3000, and 4000 RPM), with each condition tested three times. The measured parameters included engine speed, operating duration, engine temperature, and battery voltage using a tachometer, stopwatch, temperature gauge, and avometer. The results showed that the use of a fuel cell with a 180 mL reactor volume increased the engine operating duration for the same fuel volume, with an average improvement of approximately 27.5% across the three tested speed levels. However, the final engine temperature tended to be higher, and the battery voltage slightly decreased after testing. These findings indicate that a 180 mL reactor volume provides improved fuel efficiency compared with the engine condition without a fuel cell.